2016
DOI: 10.1186/s12909-016-0821-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge is not enough to solve the problems – The role of diagnostic knowledge in clinical reasoning activities

Abstract: BackgroundClinical reasoning is a key competence in medicine. There is a lack of knowledge, how non-experts like medical students solve clinical problems. It is known that they have difficulties applying conceptual knowledge to clinical cases, that they lack metacognitive awareness and that higher level cognitive actions correlate with diagnostic accuracy. However, the role of conceptual, strategic, conditional, and metacognitive knowledge for clinical reasoning is unknown.MethodsMedical students (n = 21) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
(25 reference statements)
3
20
0
6
Order By: Relevance
“…We have previously shown that additional knowledge beyond a solid factual knowledge base is not correlated with increased diagnostic competence [ 15 ]. This is in line with results that revealed that the application of different kinds of knowledge is not correlated with the diagnostic performance [ 16 ].…”
Section: Introductionsupporting
confidence: 91%
“…We have previously shown that additional knowledge beyond a solid factual knowledge base is not correlated with increased diagnostic competence [ 15 ]. This is in line with results that revealed that the application of different kinds of knowledge is not correlated with the diagnostic performance [ 16 ].…”
Section: Introductionsupporting
confidence: 91%
“…Clinical reasoning is an iterative process . It may take place rapidly and with little metacognitive guidance input, but this may increase the clinical reasoning error rate (Croskerry, 2003b;Graber, 2003;Kiesewetter et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, diagnosing is a complex skill with estimates of the number of diagnostic errors ranging in the millions . Kiesewetter et al . categorize diagnostic knowledge in (1) conceptual knowledge or what information (e.g., “Antibiotics can cause red urine as well,” p. 3), (2) procedural knowledge consisting of strategical knowledge or how information (e.g., “One could make an ultrasound scan in order to identify free fluid,” p. 3) and conditional knowledge or why information (e.g., “Chronic kidney failure – due to this, the RAAS is activated causing the hypertension.…”
Section: Clinical Reasoning In Medicinementioning
confidence: 99%